2008
DOI: 10.2106/jbjs.g.00940
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction and Internal Fixation of Capitellar Fractures with Headless Screws

Abstract: Despite the presence of greater flexion contractures at the time of follow-up in elbows with Type-IV fractures or fractures with an ipsilateral radial head fracture, good to excellent outcomes with functional ulnohumeral motion can be achieved following internal fixation of these complex fractures. Type-IV injuries may be more common than previously thought; such fractures often are associated with metaphyseal comminution or a radial head fracture and may require supplemental fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
1
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 19 publications
4
61
1
11
Order By: Relevance
“…In Ruchelsman's series, 50% of the type IV fractures identified had associated posteroinferior metaphyseal comminution and 2 fractures had separate trochlear fracture fragments. 27 In accordance with the Dubberley classification, 4 of these would have qualified as 2B fractures, and 2 as type 3 fractures. 5 Evaluation of the fractures in this manner may have further supported the present findings and those demonstrated by Dubberley that better outcomes are to be expected in large coronal fractures lacking significant comminution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ruchelsman's series, 50% of the type IV fractures identified had associated posteroinferior metaphyseal comminution and 2 fractures had separate trochlear fracture fragments. 27 In accordance with the Dubberley classification, 4 of these would have qualified as 2B fractures, and 2 as type 3 fractures. 5 Evaluation of the fractures in this manner may have further supported the present findings and those demonstrated by Dubberley that better outcomes are to be expected in large coronal fractures lacking significant comminution.…”
Section: Discussionmentioning
confidence: 99%
“…14,18,24,26,27,30 With the exception of Ruchelsman et al, all of the above studies are limited by the small patient size ranging from 4 to 6 patients. 27 Our study is unique in that it has a larger sample size than any other previously reported in the literature, allowing us to break our patients into subgroups for statistical comparison. For example, there was no difference in postoperative BM scores and ROM after headless compression screw fixation of Dubberley types-1 and -2 fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASES score can also be compared more easily with other injury states because multiple conditions have been evaluated with this scoring system. 5,6,7,12,17,19 Previous studies have attempted to identify factors that predict functional outcomes after floating elbow injury. Solomon et al 21 showed that patients with associated nerve injury have lower functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…7 Open treatments are simple, with excellent results. [12][13][14] Arthroscopic surgery has advantages, including minimized soft tissue dissection and easier evaluation of associated lesions especially involving the medial joint, although elbow arthroscopy is a challenging procedure and there are inherent risks to the neurovascular structures. 15 Holt et al stated that the criterion for arthroscopic management in articular fractures of distal humerus is capitellum fracture without comminution.…”
Section: Discussionmentioning
confidence: 99%